The crystal structure and constitution of some molecular complexes of 4:4- dinitrodiphenyl - Saunder, Douglas Harold; Saunder, Douglas Harold (Department of Physics, 2017)
The crystal structures or a number of molecular complexes formed by 4:4'-dinitrodiphenyl with various diphenyl derivatives are described. The general type of structure is undoubtedly the same for all the complexes examined and the typical arrangement may be taken as that in the complex of 4:4'-dinitrodiphenyl with 4-hydroxydiphenyl, the structure of which has been fully determined. As shown in fig. 7 the dinitrodiphenyl molecules form layers in face-centred array and lie one above the other with a spacing of about 3.7 A. The arrangement of these molecules alone is such that a set of tubular cavities, also in face-centred array, run through the structure. In the complexes these cavities are occupied by the other component molecules, the hydroxydiphenyl molecules in the case considered; which thus lie nearly normal to the planes containing the dinitrodiphenyl molecules and are seen end-on in fig. 7. In the other structures examined geometrical and symmetry conditions require that the individual molecules should be tilted in varying degrees, but the type or structure still remains essentially the same. It is shown that the ratio of the components in these complexes is determined by the length of the molecule other than dinitrodiphenyl, and that in no case is it necessary for the intermolecular distances to be shorter than those found in crystals or ordinary aromatic nitro-compounds. A bonding mechanism in terms of dipole attraction between the component molecules is shown to be consistent with all the observed data. Of interest are the periodic distortions which appear to occur in the crystal lattices of the complexes or 4:4'-dinitrodiphenyl with 4-iodo-, 4-bromo- and 4-chlorodiphenyl.